Pioneer: a synthetic human antibody phage display library for rapid therapeutic lead generation - Mateusz Putyrski; Christian Hentrich; Manuel Cavada; Melissa Wich; Sarah-Jane Kellmann; Sarah Hanselka; Michaela Eick-Werner; Hanh Hanuschka; Waldemar Preis; Christina Werkmeister; Martina Klee; Achim Knappik; et al. (mAbs)
Antibody phage display, a biotechnological method for selecting fully human antibodies from diverse libraries, is firmly established in antibody drug discovery due to its speed and flexibility. In this study, we introduce Pioneer, one of the largest synthetic human antibody libraries developed to date, with approximately 2.2 × 1011 functional members. Pioneer utilizes SpyDisplay, a phage display selection system that relies on SpyTag-SpyCatcher protein ligation technology and enables rapid selection of high-affinity antibodies. The library’s antibodies are designed for favorable biophysical properties and developability and they can be rapidly labeled or converted into various formats for screening and functional assays. We validated the performance of Pioneer in a series of selection campaigns against diverse antigens. For antibodies against four targets, TIGIT, IL-6RA, C5aR and CXCR4, we performed in-depth functional and developability characterization. For all four targets, including the two challenging G-protein coupled receptors, we demonstrated that antibodies with parameters comparable to late-stage clinical candidates can be selected directly from the library. Our results highlight the effectiveness of the Pioneer library combined with SpyDisplay in generating therapeutic lead candidates with excellent affinity, specificity, and developability, offering a robust platform for rapid antibody discovery and development.